Techno-Economic Analysis of Biogas Production from Pineapple Leaves Juice and Chicken Manure in Anaerobic Codigestion - Da Luz Castro, Juliana (2023)
Pineapple, Ananas comosus, in the one of the most important crops in Costa Rica, producing a prominent 1,7 % of the national GDP; however, current methodologies to treat pineapple leaves can cause potential public health problems due to proliferation of flies. The objective of this work was to use pineapple leaves juice to evaluate the production of biogas in combination with chicken manure as substrates. Biochemical methane potential assays were carried out using different proportions of juice and chicken manure (70/30, 80/20 and 90/10), as well as individual assays for each substrate. Results show that higher amounts of biogas were produced in the systems with 70/30 and 80/20 proportions. In addition, a capital investment estimation was carried out to evaluate the techno-economic feasibility with the Peters and Timmerhaus methodology. The techno-economic analysis gives a payback time of 2,3 years which makes the project highly profitable.